Survival in node-positive early oral squamous cell carcinoma: sentinel node biopsy versus elective neck dissection. Issue 7 (September 2022) - McMahon, Jeremy D.; Zubair, Farhan; McNicol, Scott; Hislop, W. Stuart; Salem, Saife; Howard, David; Utam, Davinder; Wales, Craig; McCaul, James
Abstract: Patients undergoing sentinel node biopsy (SLNB) for early oral squamous cell carcinoma (OSCC) who harbour occult metastases (pN+ve) may be at greater risk of mortality due to prolonged overall treatment times than those identified as pN+ve on elective neck dissection (ELND). A retrospective comparative survival analysis was therefore undertaken to test this hypothesis. Patients were identified from the South Glasgow multidisciplinary team (MDT) database. Group 1 comprised 38 patients identified as pN+ve, or who were false negative, on sentinel lymph node biopsy (SLNB). Group 2 comprised 146 patients staged pN+ve on ELND. The groups were compared with the Kaplan Meier method and Cox proportional hazards model. In addition, a matched-pair analysis was performed. A unique and specifically designed algorithm was deployed to optimise the pairings. No difference in disease-specific or overall survival was found between the groups. Patients undergoing SLNB as the initial neck staging modality in early OSCC and are identified as pN+ve do not appear to be at a survival disadvantage compared with those staged with ELND.